Double Gaze. Time, Trace, and Excess in Photography as Document - Ghezzi, Agnese (Aesthetica Preprint, 2023)
Starting from the analysis of some photographic objects and practices from the late nineteenth century selected from the archives of Italian anthropological museums, the contribution aims on the one hand to analyse how these are the product of a culturally and historically determined gaze, born in the intertwining of positivism, ethnocentrism, nationalism and colonialism. On the other hand, it aims to highlight the shifts in meaning, the presence of subjectivities that escape the hierarchical structure of the photographic device, and the impossibility of operating a control over the image. To do so, the contribution proposes a theoretical passage between the model of stereoscopic view, which can be associated with the dominant vision, and that of diplopic vision, understood as the possibility of bringing to the surface a meaning that escapes the cultural, theoretical and aesthetic framework within which the image was conceived.